Extraction of Antioxidant Compounds from Rambutan (Nephelium lappaceum L.) Peel as Agricultural Waste in Taiwan - Gusman, Josephine Azaria; Tsai, Pi-Jen (Department of Agronomy and Horticulture, IPB University, 2015)
Besides being an agricultural waste, rambutan (Nephelium lappaceum L.) peel has been widely known as good antioxidant source. However, no information about the antioxidant or their way of extraction for rambutan grown in Taiwan can be found. Since its major bioactive compound is geraniin, one of polyphenol compounds, so that total phenolic was used as an index to investigate the optimum condition of extraction from rambutan peel (red and yellow) in Taiwan. Extraction was conducted based on solvent ratio (1:10 to 1:30 g/mL), ethanol concentration (0 to 95 %), ultrasonic extraction temperature (30 to 70°C), and extraction method (conventional from 6 to 36 h at room temperature and ultrasonic from 0.5 to 10 min at 50oC). Results showed that the highest total phenolic content found in red rambutan variety was at 1:15 (g/mL) ratio, but no significant difference for yellow rambutan. Forty percent of ethanolic extraction and 50°C for ultrasonic extraction for both varieties. Conventional method (12 h) and ultrasonic method (2 min) resulted in the highest total phenolic recovery. As to their antioxidant activity in this study, FRAP ranged from 3800.25±86.49 to 4116.5±88.41 (µmol Fe2+/g D.W), flavonoid from 6.41±0.48 to 8.57±0.35 (mg Quercetin/g D.W), and total phenolic recovery from 297.78±4.06 to 358.42±4.63 (mg GAE/g D.W.). This is the first paper regarding the study of rambutan peel in Taiwan.Keywords: Rambutan (Nephelium lappaceum L.), geraniin, antioxidant, agricultural waste